THE INFLUENCE OF ALLOWANCE, FINANCIAL ATTITUDE, AND SHARIA FINANCIAL LITERACY ON THE DECISION TO SAVE IN ISLAMIC BANKS - Clara Anggita As Safa; Ahmad Zubaidi (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2024)
This study aims to analyze the influence of knowledge, religiosity and brand image on the decision of LDK UIN Jakarta members to save at Sharia Banks. This study used 25 questions. The study used primary data collected by distributing questionnaires through google-form to LDK UIN Jakarta members who had saved at Sharia Banks as many as 100 samples determined by the non-probability sampling method. The analysis technique used is Partial Least Square with SmartPLS 3.2 software. The result obtained is that knowledge has no effect on saving decisions, religiosity and brand image affect saving decisions and simultaneously knowledge, religiosity and brand image affect saving decisions. The suggestion from researchers for Islamic banks is to improve branding and conduct literacy education for the community. The suggestion for the next researcher is to use better data and theory and add research variables that are still related to this study.